IMPLEMENTASI PROGRAM BEDAH KEMISKINAN RAKYAT SEJAHTERA TERHADAP PEMBERDAYAAN MASYARAKAT DESA KALOSI KABUPATEN SIDENRENG RAPPANG - Salina Salina; Abdul Razak Useng; Andi Nilwana (JIA: Jurnal Ilmiah Administrasi, 2022)
This study aims to determine the implementation of the Prosperous People Poverty Surgery Program on Community Empowerment in Kalosi Village, Dua Pitue District, Sidenreng Rappang Regency. The population of this study was 95 people. The sampling technique used is random sampling. This type of research is quantitative descriptive. Data collection techniques are observation, questionnaire, documentation, and interviews. The data analysis technique used descriptive analysis, data quality test, classical assumption test. The results showed that the implementation of the Prosperous People Poverty Surgery Program includes communication 67%, resources 68%, disposition 69%, bureaucratic structure 69%. Community Empowerment indicators 68%, covering abilities 71%, trust 69%, authority 69%, accountability 65%. The indicator for the implementation of the Prosperous People's Poverty Program isthe category is classified as appropriate.